Public health nutrition rural, urban, and global community-based practice - Barth, M. Margaret; Bell, Ronny A.; Grimmer-Somers, Karen; Thompson, Kyle L.; Hege, Adam (Springer Publishing Company, LLC, 2021)
"Public Health Nutrition is a comprehensive, practice-based textbook for graduate and upper undergraduate students and community nutrition and public health professionals. It provides readers with the principal understanding of how improving access to healthy foods at individual, local, regional and global levels as well as improving food security and sustainability can improve community health and combat non-communicable diseases, infectious diseases, hunger and malnutrition, obesity, social injustice, and debilitating food environments. Across diverse communities, this book not only directs readers' attention towards key public health nutrition-related challenges that affect rural and urban populations across the globe, it also adds critical thinking exercises, cases, and engaging discussion to advance application of evidence-based practice in the real world"